An edge tracing method developed for object recognition - Arslan, Ahmet; Türkoğlu, İbrahim (My University, 1999)
In this study a new developed edge tracing method was applied to the pixel set formed from the numerical image of an object in order to obtain the characteristic vector which is very important in the recognition of an object. In this method, instead of detecting all elements of the pixel set, only the pixels with contour lines were traced by scanning the set for a given order. Therefore, it was shown that the edges of basic nonconvex and convex objects could be determined easily.
Bildiri - Yayımlanmış
Keywords: Object recognition; Characteristic vector; Edge tracing; Feature detection